Magnetic Susceptibility of PAlNaGd doped with Europium Glasses and its effect on MR imaging. (September 2019) - Pasanta, D; Kaewjaeng, S; Kaewkhao, J; Jumpee, C; Kothan, S; Keatwattanacharoen, S
Abstract: The effect of paramagnetic implant on magnetic resonance imaging (MRI) is important subjects in medical material studies. The purpose of this study is to investigate the effects of PAlNaGd doped with europium with the chemical composition of (60-x) P2O5: 10 Al2O3: 20 Na2O3: 10 Gd2O3: x Eu2O3, when x = 0.1 and 3.0 mol% on MR imaging. The glass was placed in phantom as to mimic in effect of material implant in human tissue. The results of this study show that artifacts severity depends on the europium ions (Eu 3+ ) concentration and T2-weighted images is more effected than that of T1-images. The T2 relaxation time is also found to be affected by the Eu 3+ concentration in the glass, causing the T2 relaxation time to become shorter. This current study found that PAlNaGd glass shows high magnetic susceptibility effects and modifies T2 relaxation time making it an interesting material for use as a medical implant and device.